Awareness and Utilization of Affordable Medicine Facility-Malaria among Caregivers of Under-Five Children in Ibadan North-West Local Government Area, Oyo State (2013)
Distribution of Affordable Medicine Facility-malaria Artemisinin CombinationTherapies (AMFm-ACTs) started in Nigeria in 2011, but its use at community level has not been documented. Methods. Four hundred seventy-eight caregivers whose under-five children had fever within two weeks prior to the survey were selected using cluster sampling technique. Information on sociodemographic characteristics, treatment seeking for malaria, and awareness and use of AMFm-ACTs was collected using an interviewer administered questionnaire. Result. More than half of the respondents (51.2%) bought AMFm-ACTs without prescription. Awareness of AMFm was low as only 9.1% has heard about the programme. Overall, 29.2% used AMFm-ACTs as their first line choice of antimalarial drug. On bivariate analysis age, group (25–34 years), public servants, respondents with tertiary education, respondents with high socioeconomic status, respondents with poor knowledge of symptoms of malaria, awareness of AMFm-ACTs, availability of AMFm-ACTs, and sources of drug were significantly associated with utilization of AMFm-ACTs (𝑃 < 0.05). Logistic regression demonstrated that only people who were aware of AMFM-ACTs predicted its use (AOR: 0.073; CI: 0.032–0.166; 𝑃 < 0.001). Conclusion. Interventions which targeted at raising awareness of AMFm-ACTs among people at risk of malaria are advocated for implementation.